A guide to mosquitoes of Australia - Webb, Cameron E.; Doggett, Stephen L.; Russell, Richard Charles; CSIRO (Clayton South, VIC : CSIRO Publishing, 2016)
Mosquitoes are annoying (and can be deadly) but they can also be beautiful. This book provides a pictorial guide to almost 100 mosquito species and includes notes on their biology, habitats and association with disease.
Introduction -- Mosquito biology -- Habitats -- Nuisance-biting and public health risks of mosquitoes -- Controlling mosquitoes around the home -- How to collect, rear and photograph mosquitoes -- Personal protection measures -- Guide to mosquito species.
"Mosquitoes are annoying, and can be deadly, but they can also be beautiful. A Guide to Mosquitoes of Australia explores the biodiversity of this fascinating group of insects. It provides a pictorial guide to almost 100 mosquito species and includes notes on their biology, habitats and association with disease. They are found in almost every type of environment, from pristine wetlands to polluted drains and from coastal saltmarshes to snow melt streams. Australia has a diverse range of mosquitoes and although relatively few pose a serious health risk, public health is an important issue. This book provides information on how to reduce the risk of mosquito-borne disease through tips on keeping your home free of mosquitoes and reducing their bites when you are out and about in the Australian environment"--Publisher's site.
Includes bibliographical references (pages 195-196) and index.
Keywords: Mosquitoes -- Australia; Mosquitoes -- Australia -- Identification; Mosquitoes -- Control -- Australia; Mosquitoes as carriers of disease -- Australia; Mosquitoes as carriers of disease; Mosquitoes; Mosquitoes -- Control; Australia; Australian; Guidebooks